2007
DOI: 10.1007/s00264-006-0278-5
|View full text |Cite
|
Sign up to set email alerts
|

A new classification and guide for surgical treatment of spinal tuberculosis

Abstract: So far, there is no widely accepted classification system based on objective findings that can serve as a guide in selecting the treatment method for spinal tuberculosis. This retrospective study evaluates patients with spinal tuberculosis (Pott's disease) treated with different surgical procedures. Our aim was to outline a new classification of spinal tuberculosis. A retrospective review of 76 cases (55 male and 25 female patients) of spinal tuberculosis was conducted. Five of the patients were treated medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
100
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 32 publications
(43 reference statements)
0
100
1
4
Order By: Relevance
“…Some authors believe that MRI and CT help in the diagnosis of TB spondylitis [10,40]. Although these have facilitated diagnosis to a great extent [6,28], biopsy is the preferred diagnostic modality [28]. MRI is the best imaging method [2,24], and shows typical diskitis, as well as epidural and paraspinal abscesses, better than any other method [24].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that MRI and CT help in the diagnosis of TB spondylitis [10,40]. Although these have facilitated diagnosis to a great extent [6,28], biopsy is the preferred diagnostic modality [28]. MRI is the best imaging method [2,24], and shows typical diskitis, as well as epidural and paraspinal abscesses, better than any other method [24].…”
Section: Discussionmentioning
confidence: 99%
“…We agree that medical therapy is the mainstay of treatment and surgery is called for only in specific conditions. The Gulhane Askeri Tip Akademisi [GATA] classification [1] mentioned by the authors gives some guidelines regarding patient and surgical management. This is similar to the ''middle path regimen'' described by Tuli [2] and followed by us.…”
mentioning
confidence: 99%
“…Spinal tuberculosis is the most common form of tuberculosis lesion [1,6,8]. Triple-drug antituberculous chemotherapy can play a main role in treating tuberculosis [5] if the lesion is without complications and limited to the vertebrae.…”
mentioning
confidence: 99%
“…Previously published studies [2,7] have reported worsening of existing symptoms or the appearance of new lesions in patients who initially responded well to antituberculous therapy. However, with proper indications, surgical procedures are considered superior regarding the prevention of neurological deterioration, maintenance of stability, and early recovery [2,[4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation